Pendampingan Peningkatan Karakter Religius di MI Miftahul Ulum Bango Solokuro Lamongan - Arifin, Ahmad; Sari, Pusvyta; Abdul Latif, Muhammad; Widyadhana, Ainur Rizqi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Character education is an effort carried out by humans consciously, in a planned manner aimed at educating and empowering the potential of students so that their personal character is formed and they become individuals who are beneficial to themselves and the surrounding environment. Therefore, a child needs assistance and education so that he can grow and develop optimally. Character education must be carried out so that children in the future can become the next generation with good personalities and dignity. The aim of this research is to describe the implementation of assistance to improve religious character through the KKN INSUD program which was carried out at Madrasah Ibtidaiyah Miftahul Ulum Bango, Payaman, Solokuro, Lamongan. Activities to improve religious character are carried out by getting the following activities: morning assembly prayer, reading al quran before starting learning, Dhuha prayer, midday prayer, wearing Muslim and Muslim clothes, shaking hands with teachers and commemorating Islamic holidays.